Prioritizing the Development of Indonesian Culinary Businesses Over the Legal Transition of International Food Businesses in Relation to Traditional Nusantara Cuisine - Kusnedi, Rahmat; Arafah, Willy; Ingkadijaya, Rahmat; Oktadiana, Hera (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Traditional food from different parts of Indonesia is very diverse. However, the growth of Nusantara’s culinary business often faces problems, both in terms of legislation and competition with the growing foreign food business. Compared to food business laws in other countries that are more organized and supportive, Indonesian laws that regulate the protection and promotion of traditional foods are often uncompetitive. National food business law resistance to traditional Nusantara food is one of the obstacles to the growth of Nusantara's culinary business. More expert strategies are needed to improve the competitiveness of traditional food products as Indonesian traditional food trends continue to shift due to imported food. Behavioral theories that focus on perception, subjective norms, and behavioral control are used in this study to measure how millennials use Indonesian food. The results show that consumers have a good perception of local food. However, the lowest average value of all variables suggests that the perceptions of important people do not influence them dominantly in consuming local foods. Therefore, there is a need for efforts to raise public awareness and concern for traditional Nusantara food as well as to increase professionalism in the development of the Nusantara culinary business. Keywords: Nusantara's culinary business, food business law, traditional food, regulation, protection of intellectual property rights